Suicide and Adolescence - Harris, Tracey E. (International journal of offender therapy and comparative criminology, 1993)
The present study investigates the role of family background, substance abuse, depression, and hopelessness in predicting past suicidal behaviour in 47 incarcerated juvenile delinquents. Depression was found to be the best predictor of both suicidal ideation and suicide attempt. Aside from depression, no other factors achieved significance for predicting suicide risk, although suicide ideation significantly predicted suicide attempts